Tinjauan Literatur Sistematis tentang Mindfulness Buddhis dalam Pendidikan - Khie Khiong; Shelfia Angela; Fendy Fendy; Pedi Kurniawan (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This research presents a systematic literature review (SLR) on the application of Buddhist mindfulness in an educational context. Using a meta-synthesis approach and the PRISMA protocol, this study analyzes 19 selected scholarly articles from the Dimensions database. The analysis reveals that Buddhist mindfulness plays a significant role in reducing psychological stress, improving mental well-being, and supporting both students' and educators' academic and socio-emotional capacities. Its implementation takes various forms, ranging from integration into curriculum and pedagogy and specialized training programs to contextual adaptations that are sensitive to local culture and values. However, its application faces challenges such as secularization (McMindfulness), religious sensitivity, limited resources, and variations in research methodology. Successful implementation is highly dependent on mindful leadership, adequate teacher training, and the creation of a safe and inclusive environment. This review highlights the need for future longitudinal studies, an integrated approach between policy and practice, and the development of authentic and locally relevant mindfulness models to achieve a holistic and sustainable educational transformation.